Financial flexibility and the choice between dividends and stock repurchases - Jagannathan, M (Journal of Financial Economics, 2000)
This paper measures the growth in open market stock repurchases and the manner in which stock repurchases and dividends are used by U.S. corporations. Stock repurchases and dividends are used at different times from one another, by different kinds of firms. Stock repurchases are very pro-cyclical, while dividends increase steadily over time. Dividends are paid by firms with higher “permanent” operating cash flows, while repurchases are used by firms with higher “temporary”, non-operating cash flows. Repurchasing firms also have much more volatile cash flows and distributions. Finally, firms repurchase stock following poor stock market performance and increase dividends following good performance. These results are consistent with the view that the flexibility inherent in repurchase programs is one reason why they are sometimes used instead of dividends.